Banff 2016 Global Assessment and Quantitative Scoring for T Cell-Mediated Liver Transplant Rejection are Interchangeable - Maryam Eghtedari; Catriona McKenzie; Lauren C. Y. Tang; Avik Majumdar; James G. Kench (Journal of Transplantation, 2023)
Introduction. Histopathological assessment of liver biopsies is the current “gold standard” for diagnosing graft dysfunction after liver transplantation (LT), as graft dysfunction can have nonspecific clinical presentations and inconsistent patterns of liver biochemical dysfunction. Most commonly, post-LT, graft dysfunction within the first year, is due to acute T-cell mediated rejection (TCMR) which is characterised histologically by the degree of portal inflammation (PI), bile duct damage (BDD), and venous endothelial inflammation (VEI). This study aimed to establish the relationship between global assessment, which is the global grading of rejection using a “gestalt” approach, and the rejection activity index (RAI) of each component of TCMR as described in revised Banff 2016 guidelines. Methods. Liver biopsies (n = 90) taken from patients who underwent LT in 2015 and 2016 at the Australian National Liver Transplant Unit were identified from the electronic medical records. All biopsy slides were microscopically graded by at least two assessors independently using the revised 2016 Banff criteria. Data were analysed using IBM SPSS v21. A Fisher–Freeman–Halton test was performed to assess the correlation between the global assessment and the RAI scores for each TCMR biopsy. Results. Within the cohort, 60 (37%, n = 164) patients underwent at least 1 biopsy within 12 months after LT. The most common biopsy outcome (total n = 90) was acute TCMR (64, 71.1%). Global assessment of TCMR slides strongly positively correlated with PI (p value <0.001), BDD (p value <0.001), VEI (p value <0.001), and total RAI (p value <0.001). Liver biochemistry of patients with TCMR significantly improved within 4 to 6 weeks post-biopsy compared to the day of the biopsy. Conclusion. In acute TCMR, global assessment and total RAI are strongly correlated and can be used interchangeably to describe the severity of TCMR.